2011
DOI: 10.5402/2011/907493
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Dyeing of 80 : 20 Polyester/Cotton Blended Fabric Using Disperse and Reactive Dyes

Abstract: Polyester/Cotton blended fabrics are normally dyed by two-bath or one-bath two-step dyeing method. This paper deals with a new approach involving azeotropic ternary mixture of organic solvents pretreatment to dye polyester/cotton blends using disperse and reactive dyes in one-bath method. The effect of solvent pretreatments on dyeability, fastness, and few physicochemical properties has been investigated involving SEM, FTIR, DSC, and XRD studies, and results are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Thus, discharge of disperse dyes have become a subject of concern in the universe due to its harmful and toxic effects to living organisms and the environment [ 143 ]. As far as the wastewater treatment technologies are concerned, different techniques have been utilized for the reduction and degradation of dispersed dyes such as chemical precipitation, H 2 O 2 adsorption, oxidation by chlorine, electrochemical treatment, ozone electrolysis, adsorption, ion pair extraction, flocculation, coagulation, membrane filtration, and specially the photocatalytic process [ 145 147 ].…”
Section: Photocatalytic Decolorization Of Synthetic Dyesmentioning
confidence: 99%
“…Thus, discharge of disperse dyes have become a subject of concern in the universe due to its harmful and toxic effects to living organisms and the environment [ 143 ]. As far as the wastewater treatment technologies are concerned, different techniques have been utilized for the reduction and degradation of dispersed dyes such as chemical precipitation, H 2 O 2 adsorption, oxidation by chlorine, electrochemical treatment, ozone electrolysis, adsorption, ion pair extraction, flocculation, coagulation, membrane filtration, and specially the photocatalytic process [ 145 147 ].…”
Section: Photocatalytic Decolorization Of Synthetic Dyesmentioning
confidence: 99%
“…This is as a result of greater stability conferred by the solvents on the treated fibres. The increase in the strength and stability of the treated materials can be ascribed to the improvements in the structural order of the polymer matrix and generation of more number of crystallites leading to improvement in the resistance power to deform the materials with higher inter chain bond [11]. The results obtained here are similar to available reports available on the effects of solvent pretreatments on polymer wherein the solvents do not penetrate the compact crystalline region in the polymer and therefore do not adversely affect the strength of the materials [10].…”
Section: Tenacitymentioning
confidence: 99%
“…Dyeing of polyester/cotton blends poses some challenges to dyer as polyester shows a hydrophobic character while cotton shows a hydrophilic character making it inevitable to dye them with a chemically different class of dyes [8,9]. Muralidharan and Laya [10], found that Polyester/cotton blended fabrics are often coloured using a two-bath or onebath two-step dyeing process. It discusses a new method for dyeing polyester/cotton blends utilizing dispersion and reactive dyes in a one-bath procedure that uses an azeotropic ternary mixture of organic solvents as a pretreatment.…”
Section: Introductionmentioning
confidence: 99%
“…These dying techniques, on the other hand, are time-consuming and difficult. The process of the one-bath two-step dyeing process is shorter than the two-bath method but its disadvantage is lower dyeability from migration and poor reproducibility since two different sorts of dyes are utilized in an equivalent bath [10]. The one-bath one-step dyeing process of polyester/cotton blends with disperse/ reactive dyes has advantages over the conventional dyeing processes on reducing the dyeing cycle as well as energy consumption [16].…”
Section: Introductionmentioning
confidence: 99%